Chasing the clouds away : a novel - Macomber, Debbie (Ballantine Books, 2026)
"Maisy Gallagher has her own dreams, but when her father passes away, she selflessly sets them aside to help her family. Despite knowing it was the right thing to do, she can't help but wish for the road not taken. Chase Furst, the hardened heir to a financial empire, is on the other hand primarily focused on his own life and on his work as a bank executive. His childhood was marred by his mother's struggle with addiction, and left him cynical and emotionally distant. But then Chase meets Maisy, a beautiful woman full of optimism and kindness who can see past his defenses. To his surprise and annoyance, she offers to help him during a time of need, and declines his offer of payment. Instead, she asks him to pay it forward -- and not with money or a quick fix, but through an act of true selflessness. At a loss, Chase doesn't know where to begin." --